2018
DOI: 10.1002/qj.3205
|View full text |Cite
|
Sign up to set email alerts
|

Strong winds in a coupled wave–atmosphere model during a North Atlantic storm event: evaluation against observations

Abstract: Strong winds may be biased in atmospheric models. Here the European Centre for Medium-range Weather Forecasts (ECMWF) coupled wave-atmosphere model is used (i) to evaluate strong winds against observations, and (ii) to test how alternative wind stress parametrizations could lead to a more accurate model. For the period of storms Kaat and Lilli (23-27 January 2014), we compared simulated winds with in situ -moored buoys and platforms -and satellite observations available from the North Atlantic. Five wind stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 53 publications
6
27
0
Order By: Relevance
“…Taking advantage of an extremely active 2017 hurricane season in the tropical Atlantic Ocean and the Eastern Pacific soon after the launch of the CYGNSS mission, we revisited some of the main parametric wind models used for storm surge hazard assessment or prediction of cyclonic waves, and investigated the potential of recent remote sensing data to estimate surface wind speeds under extreme conditions. Using an innovative approach, we first confirmed the findings of a number of previous studies: the inability of ASCAT data to reproduce strong winds for instance [51], or systematic bias in several parametric models, as stated by Willoughby et al [39], Lin and Chavas [17] or Chavas et al [47]. All these results are displayed in a "user-friendly" figure (Figure 2) that should be helpful for the readers to identify the model most suited for their case study.…”
Section: Discussionsupporting
confidence: 80%
“…Taking advantage of an extremely active 2017 hurricane season in the tropical Atlantic Ocean and the Eastern Pacific soon after the launch of the CYGNSS mission, we revisited some of the main parametric wind models used for storm surge hazard assessment or prediction of cyclonic waves, and investigated the potential of recent remote sensing data to estimate surface wind speeds under extreme conditions. Using an innovative approach, we first confirmed the findings of a number of previous studies: the inability of ASCAT data to reproduce strong winds for instance [51], or systematic bias in several parametric models, as stated by Willoughby et al [39], Lin and Chavas [17] or Chavas et al [47]. All these results are displayed in a "user-friendly" figure (Figure 2) that should be helpful for the readers to identify the model most suited for their case study.…”
Section: Discussionsupporting
confidence: 80%
“…with T p the peak period of the waves and g the acceleration of gravity. 20 Keeping the coefficients A and B constant with wind speed results in drag coefficient and wind stress too strong in strong wind conditions (wind speed above 20 m.s −1 ) as shown by Pineau-Guillou et al (2018). In order to tackle this, and to reproduce the saturation or the decrease of the drag coefficient observed in strong to cyclonic winds (e.g.…”
Section: Wave Impact On the Charnock Coefficientmentioning
confidence: 99%
“…Using the former formulation of Oost et al (2002) in high-resolution numerical experiments of HPE, Thévenot et al (2016) and Bouin et al (2017) showed an impact on the location of precipitation when the sea state forcing is taken into account in the sea surface turbulent fluxes parametrization. Nevertheless, these formulas are known to produce too 20 strong fluxes when strong winds (>20 m.s −1 ) are encountered (Pineau-Guillou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these contributors, wind-waves play an important role on sea level at the coast (for a full discussion see Dodet et al, this issue), either directly, or indirectly through their influence on the wind stress and storm surge (e.g. Mastenbroek et al 1993, Pineau-Guillou et al 2018, and their role on the morphodynamic evolution of the nearshore (Coco et al, 2014;Masselink et al, 2016). Over the ocean shelves and along the coasts, ocean mass variations, reflected in ocean bottom pressure changes, are one of the dominant components of sea-level variability.…”
Section: Introductionmentioning
confidence: 99%